Penerapan Restorative Justice pada Pencemaran Nama Baik di Media Sosial Perspektif UU ITE 2024 - Herni Herni; Fitri Wahyuni; Bambang Sasmita Adi Putra (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The development of information technology and social media has transformed patterns of public communication and increased the number of defamation cases in the digital sphere. This condition has created legal challenges because the conventional criminal justice approach is considered insufficiently proportional to conflicts that often stem from social relationships, communication misunderstandings, or momentary emotions. This study aims to analyze the regulation of criminal acts of defamation through social media, the implementation of the restorative justice approach, and its effectiveness based on Law Number 1 of 2024 concerning Electronic Information and Transactions. The research employs a normative juridical method using statutory and conceptual approaches through library research, followed by qualitative analysis. The findings indicate that the regulation of defamation has been further strengthened through the harmonization of criminal and civil legal norms. The implementation of restorative justice involves community institutions and relevant authorities; however, it still faces challenges, including the lack of digital mediation guidelines, low levels of digital literacy, and ambiguity regarding the elements of the criminal offense.